Analisis Semiotika Pola Komunikasi Keluarga pada Film “Noktah Merah Perkawinan” - Utami, Nur Taqwa; Hastuti, Hastuti; Putra, Muh. Rizal Ardiansah (JOPPAS: Journal of Public Policy and Administration Silampari, 2024)
The film 'Noktah Merah Perkawinan' tells the story of a married couple who have been married for several years and have two children. The communication patterns between the characters Gilang and Ambar depict events that reflect realities often observed in society, such as conflicts within a household. Therefore, the objective of this research is to analyze the semiotics of family communication patterns in the film 'Noktah Merah Perkawinan.' This research employs the semiotic analysis method of Ferdinand De Saussure, which comprises two elements: signifier and signified. Additionally, the research categorizes communication patterns based on De Vito's classification, including monopolistic family communication, balanced separate communication, unbalanced separate communication, and equality communication. According to this classification, the findings reveal that in monopolistic communication patterns, one party significantly dominates based on their influence within the family. In the case of balanced separate family communication, each family member plays their respective roles. Unbalanced separate communication occurs when communication within the family involves only one individual dominating due to their perceived expertise on a particular issue. In contrast, equality communication is characterized by open communication among family members without any specific restrictions. In conclusion, the research demonstrates that family communication patterns in this film vary widely, with each family member having their distinct role. Moreover, it suggests that all conflicts depicted in the film 'Noktah Merah Perkawinan' can be resolved through effective communication without any imposed limitations, as seen in the equality communication pattern. Keywords: Noktah Merah Perkawinan, Family Communication Patterns, Semiotic